2021
DOI: 10.1016/j.jiac.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study using IgM and IgG antibody titers against SARS-CoV-2 in The University of Tokyo, Japan (UT-CATS)

Abstract: Introduction The worldwide pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has continued to date. Given that some of the patients with coronavirus disease 2019 (COVID-19) are asymptomatic, antibody tests are useful to determine whether there is a previous infection with SARS-CoV-2. In this study, we measured IgM and IgG antibody titers against SARS-CoV-2 in the serum of asymptomatic healthy subjects in The University of Tokyo, Japan. Methods Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, this study is a time-series large population study, and our study focuses on the macroscopic relationship between the overall serum antibodies level and positive rate with time; thus, the results of the study may not be consistent with other studies. Finally, Serum SARS-CoV-2 IgG antibody kits used in his study are different from others used in the previous reports, and the results of the study are closely related to the cutoff values set by different manufacturers because the reagent manufacturers need to comprehensively consider the specificity and sensitivity of the detection method to set cutoff values [18,22]. Therefore, our results reflected the actual seropositivity level of IgG and the status of herd immunity of the resident population in that period.…”
Section: Discussionmentioning
confidence: 67%
“…However, this study is a time-series large population study, and our study focuses on the macroscopic relationship between the overall serum antibodies level and positive rate with time; thus, the results of the study may not be consistent with other studies. Finally, Serum SARS-CoV-2 IgG antibody kits used in his study are different from others used in the previous reports, and the results of the study are closely related to the cutoff values set by different manufacturers because the reagent manufacturers need to comprehensively consider the specificity and sensitivity of the detection method to set cutoff values [18,22]. Therefore, our results reflected the actual seropositivity level of IgG and the status of herd immunity of the resident population in that period.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, the results revealed that smokers had lower levels of vaccine-induced antibodies than nonsmokers as well as an increase in IgG-N levels in smoker individuals due to the elevated susceptibility to infection, which is consistent with earlier research. 36 , 37 , 38 , 39 More research is needed into the mechanisms through which cigarette smoke decreases immunological responses to COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%